PENGARUH GAYA KEPEMIMPINAN PATH GOAL THEORY TERHADAP INOVASI PENGAJARAN PADA LEMBAGA PENDIDIKAN ISLAM DI LOMBOK - Husna, Fathonatul Aulia Il; Citriadin, Yudin; Hermansyah, Hermansyah (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the effect of Path Goal Theory leadership style on teaching innovation in Islamic educational institutions in Lombok. The approach used is quantitative with correlational research type, with purposive sampling consisting of teachers in several Islamic schools. The research instrument was a five-point Likert scale questionnaire developed based on four dimensions of the Path Goal leadership style (directive, supportive, participative, and achievement-oriented) and indicators of teaching innovation. Data were collected through Google Form and analyzed using descriptive statistics and simple linear regression through JASP software. The results of the analysis showed that Path Goal Theory leadership style had a significant effect on teaching innovation, with an R² value of 0.455 and a significance of p < 0.001. That is, 45.5% of the variation in teaching innovation can be explained by this leadership style. The findings confirm the importance of adaptive leadership in creating innovative learning environments in Islamic education institutions. The study recommends that institutional leaders develop leadership styles that suit teachers' needs to support educational transformation.